2014
DOI: 10.1080/00981389.2014.896847
|View full text |Cite
|
Sign up to set email alerts
|

“We’re Just Targeted as the Flock That Has HIV”: Health Care Experiences of Members of the House/Ball Culture

Abstract: The house/ball community is an understudied sub-group of young Black men who have sex with men and transgender persons in urban centers of the United States who affiliate in social structures called houses and gather at elaborate dance and performance events called balls. In Charlotte, North Carolina, 12 house/ball members were interviewed about their experiences with health care providers and their assessment of any barriers to care due to their affiliation with the rather clandestine house/ball sub-culture. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 13 publications
0
28
0
Order By: Relevance
“…11 Our findings also agree with research suggesting that men can feel stigmatized when providers immediately associate MSM behavior with HIV risk. 42 Our results can contribute to literature on building cultural competence among clinical providers serving MSM and other sexual minority populations. [43][44][45][46][47][48][49][50][51][52][53] We also support recent calls for increased clinical training and cultural competency in MSM healthcare.…”
Section: Discussionmentioning
confidence: 74%
“…11 Our findings also agree with research suggesting that men can feel stigmatized when providers immediately associate MSM behavior with HIV risk. 42 Our results can contribute to literature on building cultural competence among clinical providers serving MSM and other sexual minority populations. [43][44][45][46][47][48][49][50][51][52][53] We also support recent calls for increased clinical training and cultural competency in MSM healthcare.…”
Section: Discussionmentioning
confidence: 74%
“…Table 1 summarizes the study design, purpose, data collection method, inclusion and exclusion criteria, sample size, and main findings of the nineteen peer-reviewed studies identified for evaluation regarding health and well-being of HBCs. The table lists the articles in alphabetical order by (Olivas, et al 2019 (Rowan, DeSousa, Randall, White & Holley, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the work completed with the HBC has emphasized the structure of the Houses and their role in HIV prevention (Dickson-Gomez et al, 2014;Kipke, Kubicek, Supan, Weiss, & Schrager, 2013;Murrill, 2008;Phillips, Peterson, Binson, Hidalgo, & Magnus, 2011;Sanchez, Finlayson, Murrill, Guilin, & Dean, 2010;Schrager, Latkin, Weiss, Kubicek, & Kipke, 2014); supportive networks and social structures (Arnold, Sterrett-Hong, (Olivas, et al 2019 (Holloway et al, 2012;Kipke, Kubicek, Supan, Weiss, & Schrager, 2013;; and, partnerships and collaborations (Alio et al, 2014;Castillo, Palmer, Rudy, & Fernandez, 2012). The remaining studies addressed specific health topics related to HIV, such as stigma, (Galindo, 2013), resilience , and access to health care (Rowan, DeSousa, Randall, White, & Holley, 2014). (Olivas, et al 2019) Exploring Health and Wellbeing in the US House Ball Community: A Systematic Review (Olivas, et al 2019) Exploring Health and Wellbeing in the US House Ball Community: A Systematic Review from within the community are most ideal given member experiences with homophobia and stigmatization from outside of the community.…”
Section: Study-specific Findingsmentioning
confidence: 99%
See 2 more Smart Citations